CONTRIBUTION OF ORGANIZATIONAL CLIMATE AND MOTIVATION TO TEACHER SATISFACTION AND PERFORMANCE - Arji Yunandar; Musdiani Musdiani; Sariakin Sariakin (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study aims to analyze the direct influence of organizational climate, work motivation, and job satisfaction on the performance of teachers at SD Negeri Gugus 1 Suka Damai, Lembah Seulawah District, and to build a causal relationship model between these variables. The approach used is quantitative with a causal design. Data collection used a questionnaire that had been tested for validity and reliability, while the analysis was carried out using path analysis techniques. The results of the study showed that organizational climate had a significant effect on teacher job satisfaction (r = 0.352; 12.3%), as well as work motivation (r = 0.298; 8%). Organizational climate also had a direct effect on teacher performance (r = 0.621; 38.5%), followed by the influence of work motivation (r = 0.328; 10.7%) and job satisfaction (r = 0.710; 50.4%). The relationship model between exogenous and endogenous variables that was built was proven to be empirically valid. These findings indicate that improving organizational climate, work motivation, and job satisfaction can effectively encourage improved teacher performance. Therefore, strengthening these three aspects is highly recommended in efforts to improve the quality of education in elementary schools.